Impact assessment of e-commerce integration on the key performance indicators of food and beverage micro enterprises in Tacloban City - Crame, Flora Mae; Dacuyan, Flordeliz B.; Doming, Gennel C.; Morden, Thea Shaira G. (2024)
This study was conducted to determine the impact of e-commerce integration on key performance indicators by measuring the effect of integration through key indicators such as sales growth, customer base, customer satisfaction, and process enhancement. The study also presented the key internal organizational factors and external market-related factors that influence the businesses' decision to integrate e-commerce. Using descriptive design and purposive sampling to gather respondents, a non-guided survey was conducted among 124 food and beverage micro enterprises in Tacloban City. Facebook is the most utilized platform; which is closely followed by emerging applications namely mobile payments like GCash and Maya, and Maxim. Most food and beverage microbusinesses in Tacloban City are classified as having basic e-commerce integration, which means that they only utilize e-commerce for communication purposes. Also, the majority utilize e-commerce both in buying supplies and selling goods. The predominant internal motivator is to increase profitability, while the second factor trailing behind is to reduce costs which contribute to increasing profitability. On the other hand, the external factors that pushed these owners to integrate e-commerce into their business are the popularity of e-commerce platforms and pressure from consumers to adopt e-commerce in their business. The findings suggest that e-commerce integration is an effective strategy for microbusiness owners of food and beverage stores in Tacloban City to be more competitive. All of the key performance indicators sales growth, customer base, customer satisfaction, and process enhancement have been improved through the use of e-commerce, thus making these businesses more competitive.
Undergraduate thesis (B.S. Accountancy) -- University of the Philippines, Tacloban.